Studies on the wing colour patterns and isozyme variability in two species of froghoppers - Perondini, A. L.P.; Mori, Lyria; Morgante, J. S. (Pesquisa Agropecuaria Brasileira, 2014)
The enzymatic polymorphism coded by twelve loci was studied in a population of Zulia entreriana and Deois flavopicta. Both species bear a substancial degree of genetic variability presenting 18 and 27% of their loci polymorphic, 1.18 and 1.36 as the mean number of alleles per locus, and 6.1 and 4.6% of heterozigosity, respectively for Z. entreriana and D. flavopicta. Nei's genetic similarity index between them was of 0.705. Z. entreriana is highly polymorphic for the wing colour stripes, showing eight different patterns. A single variant morph was detected in D. flavopicta. The isozyme variability of six loci was studied in specimens of Z. entreriana, pooled according to the wing patterns. The genetic similarity among these groups varied from 0.962 to 0.999. These data, processed to produce a biochemical similarity dendrogram, indicate the existence of three sub-populations each showing a distinct colour pattem and specific gene frequencies.